Major Antigenic Proteins of the Agent of Human Granulocytic Ehrlichiosis Are Encoded by Members of a Multigene Family - Murphy, Cheryl I. (American Society for Microbiology, 1998)
Western blot analysis of proteins from a cell culture isolate (USG3) of the human granulocytic ehrlichiosis (HGE) agent has identified a number of immunoreactive proteins, including major antigenic proteins of 43 and 45 kDa. Peptides derived from the 43- and 45-kDa proteins were sequenced, and degenerate PCR primers based on these sequences were used to amplify DNA from USG3. Sequencing of a 550-bp PCR product revealed that it encodes a protein homologous to the MSP-2 proteins of Anaplasma marginale. Concurrently, an expression library made from USG3 genomic DNA was screened with granulocytic Ehrlichia (GE)-positive immune sera. Analysis of two clones showed that they contain one partial and three full-length highly related genes, suggesting that they are part of a multigene family. Amino acid alignment showed conserved amino- and carboxy-terminal regions which flank a variable region. The conserved regions of these proteins are also homologous to the MSP-2 proteins of A. marginale; thus, they were designated GE MSP-2A (45 kDa), MSP-2B (34 kDa), and MSP-2C (38 kDa). The PCR fragment obtained as a result of peptide sequencing was completely contained within the msp-2A clone, and all of the sequenced peptides were found in the GE MSP-2 proteins. Recombinant MSP-2B protein and an MSP-2A fusion protein were expressed in Escherichia coli and reacted with human sera positive for the HGE agent by immunofluorescence assay. These data suggest that the 43- and 45-kDa proteins of the HGE agent are encoded by members of the GE MSP-2 multigene family.